2012
DOI: 10.1177/1352458512447597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pattern-reversal visual evoked potential in patients with neuromyelitis optica

Abstract: Evaluation of VEP in patients with definite NMO revealed a pattern that is different from that of MS in 81.6% of eyes examined, characterized by the absence of responses, or decreased amplitude with normal latency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 24 publications
4
35
1
4
Order By: Relevance
“…Among the 38 eyes examined, 18 (47%) had no VEP responses and 13 (34%) had reduced P100 amplitudes with normal latency. From their findings the authors concluded that VEP findings in NMO patients were distinctive, specifically 82% of eyes showed absent responses or decreased amplitudes, as opposed to the pattern typically seen in MS patients characterized by delayed p100 latencies with no change in amplitude in 60-100% of cases [26]. It noteworthy, however, that the aforementioned VEP findings may reflect the severity of the optic nerve injury, and do differentiate the pathobiology of the optic nerve insult in NMO-ON eyes related to MS-ON or sporadic ON eyes.…”
Section: Visual Evoked Potentialsmentioning
confidence: 87%
See 1 more Smart Citation
“…Among the 38 eyes examined, 18 (47%) had no VEP responses and 13 (34%) had reduced P100 amplitudes with normal latency. From their findings the authors concluded that VEP findings in NMO patients were distinctive, specifically 82% of eyes showed absent responses or decreased amplitudes, as opposed to the pattern typically seen in MS patients characterized by delayed p100 latencies with no change in amplitude in 60-100% of cases [26]. It noteworthy, however, that the aforementioned VEP findings may reflect the severity of the optic nerve injury, and do differentiate the pathobiology of the optic nerve insult in NMO-ON eyes related to MS-ON or sporadic ON eyes.…”
Section: Visual Evoked Potentialsmentioning
confidence: 87%
“…VEP testing has been reported to reveal abnormalities in NMO-ON that differ from the classic features of MS-ON. In a recent study by Neto et al, 19 NMO patients underwent pattern reversal VEP testing [26]. Among the 38 eyes examined, 18 (47%) had no VEP responses and 13 (34%) had reduced P100 amplitudes with normal latency.…”
Section: Visual Evoked Potentialsmentioning
confidence: 99%
“…We can conclude that VEP has recently been sufficiently studied and shows differences between the classic pattern of MS and that of NOM, where the responses are more heterogeneous, and the reduction of P100 wave amplitude and the absence of response are more prevalent [34], but data in the literature are lacking about the VEP pattern in RION, CRION, syndromes of the NOM spectrum, and OSMS of MS. …”
Section: Discussionmentioning
confidence: 99%
“…Seven (35%) had amplitudes ≥ 5.8 μV, being considered normal. In 65% of the 20 eyes where the visual response was evocable, a reduction of the P100 wave amplitude was found, with normal latency [34].…”
Section: Vep In Idiopathic Inflammatory Demyelinating Diseasesmentioning
confidence: 99%
See 1 more Smart Citation